Distribution and diversity of phytoplankton in a tropical man-made lake, Putrajaya, Malaysia - Jamal, Asma' (2015)
A study on phytoplankton community in a tropical man-made lake, Putrajaya Lake was carried out from October 2009 to September 2010. The study was conducted to examine the phytoplankton composition, distribution and diversity in different zones of the lake, and in different seasons. Monthly phytoplankton samples were collected at three selected stations representing three different lake zones, namely Station 1 (littoral zone), Station 2 (sub-littoral zone) and Station 3 (limnetic zone). Phytoplankton samples from each station were preserved, identified and enumerated. Physicochemical parameters such as water temperature, pH, conductivity and dissolved oxygen were measured in situ. Meteorological data were obtained from the Putrajaya Corporation Database Centre. Differences in the composition and diversity of the community across zones spatially and vertically were analysed by using multivariate test procedures. A total of 148 species from 77 genera were recorded for the Putrajaya Lake during the study period. The seven identified groups were Chlorophyta (59% of the total abundance), Pyrrhophyta (15%), Cyanobacteria (11%), Bacillariophyceae (9%), Chrysophyceae (3%), Cryptophyta (2%) and Euglenophyta (1%). The highest total mean density of phytoplankton was recorded in the limnetic zone (433.94 ± 18.29 cells ml-1), followed by sub-littoral (292.94 ± 18.61 cells ml-1) and littoral zone (199.58 ± 13.56 cells ml-1). Average similarity within zones in descending order was limnetic zone (58.5%), sublittoral zone (53.7%) and littoral zone (52.1%). According to zones, Peridinium had the highest density in littoral and sub-littoral zones although the dinoflagellates were not the dominant phytoplankton group, whereas Staurastrum dominated the limnetic zone. There was a significant difference in the Shannon-Wiener diversity index for phytoplankton diversity and abundance in all three zones (p < 0.05). Limnetic zone demonstrated the highest species diversity (H’=3.48 ± 0.021) compared to other zones. In terms of depth distribution, the highest phytoplankton density was found at 1.5 m depth (366.03 ± 33.37 cells ml-1) combining all stations. However, the highest species diversity was observed at 2.0 m depth (3.54 ± 0.04). Nonetheless, densities and species diversity values at different depths were not significantly different (p > 0.5). Two distinct groups consisted of limnetic and littoral-sub-littoral zones at 83% were obtained from the dendrogram. SIMPER average dissimilarity was highest between littoral and limnetic zone (50.8%) with Staurastrum as the most discriminating genus (6.7%). Sub-littoral species dominated both littoral and limnetic phytoplankton communities suggesting that sub-littoral zone acts as an interphase for phytoplankton adaptation and migration between the two different zones. Phytoplankton community in Putrajaya Lake did not show distinct seasonal pattern. Rainfall had low influence on the phytoplankton community structure (r = 0.168) and the ANOSIM R value (R = 0.21) indicated strong overlapping of phytoplankton communities found during the wet and dry seasons. Average dissimilarity between the two seasons was 49.8% whilst average similarity within each wet and dry seasons were 55.0% and 58.5%, respectively. Shannon-Wiener diversity index during the wet season was higher than the dry season, but not significantly different (p > 0.05). Physical parameters such as water transparency, temperature, pH, dissolved oxygen, and conductivity were found to be important factors characterizing each zone and influencing the phytoplankton composition (p < 0.01). The genus Staurastrum and Peridinium which were found dominant in the present study may indicate the water trophic as oligotrophic. Nevertheless the rise and sink of chrysophytes at a certain period of time may suggest the interchanging trophic water between oligotrophic to mesotrophic. The findings suggest that spatial and temporal distribution and diversity of the phytoplankton community can be affected significantly by local lake zonation characterized by environmental variations.